2021
DOI: 10.3390/children8111061
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-Child Health Outcomes from Pre- to Post-Implementation of a Trauma-Informed Care Initiative in the Prenatal Care Setting: A Retrospective Study

Abstract: Background: There has been an increase in use of trauma-informed care (TIC) approaches, which can include screening for maternal Adverse Childhood Experiences (ACEs) during prenatal care. However, there is a paucity of research showing that TIC approaches are associated with improvements in maternal or offspring health outcomes. Using retrospective file review, the current study evaluated whether differences in pregnancy health and infant birth outcomes were observed from before to after the implementation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…These include addressing healthcare workforce shortages and health infrastructure challenges to alleviate limited clinic interaction time, inadequate physical spaces to reduce privacy issues and support consult-room and triage-level IPV screening respectively. Training healthcare workers using trauma-informed care-based approaches and implementation in ANC settings [ 62 , 67 ] may increase clinicians’ ability to realize the burden of trauma, recognize how all individuals involved with systems, organizations are affected by trauma and respond by putting this knowledge into practice. Providers posited the need to address safety concerns raised by some IPV survivors about retaliatory partner abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include addressing healthcare workforce shortages and health infrastructure challenges to alleviate limited clinic interaction time, inadequate physical spaces to reduce privacy issues and support consult-room and triage-level IPV screening respectively. Training healthcare workers using trauma-informed care-based approaches and implementation in ANC settings [ 62 , 67 ] may increase clinicians’ ability to realize the burden of trauma, recognize how all individuals involved with systems, organizations are affected by trauma and respond by putting this knowledge into practice. Providers posited the need to address safety concerns raised by some IPV survivors about retaliatory partner abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Training healthcare workers using trauma-informed care-based approaches and implementation in ANC settings [ 62 , 67 ] may increase clinicians’ ability to realize the burden of trauma, recognize how all individuals involved with systems, organizations are affected by trauma and respond by putting this knowledge into practice.…”
Section: Discussionmentioning
confidence: 99%
“…It is the position of the guest editors of this Special Issue that screening is a necessary and helpful component to a more comprehensive trauma-informed healthcare system. Four papers (Racine et al [ 5 ], Herrero-Roldan et al [ 6 ], Olecka [ 7 ], and Matthew et al [ 8 ]) in this issue were devoted to identifying the benefits of preventing and implementing a trauma-informed approach to care.…”
mentioning
confidence: 99%
“…Limited research exists on TIC approaches implemented within the prenatal care setting. Studies such as Racine et al [ 5 ] have identified some associations between TIC approaches and positive health aspects in infant outcomes. Specifically, as reported in Racine et al [ 5 ], comparing groups receiving standard care versus a TIC approach at two points in time, infants of mothers receiving TIC had significantly fewer adverse birth outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation